A comparison between sitagliptin or glibenclamide in addition to metformin + pioglitazone on glycaemic control and β‐cell function: the triple oral therapy. Issue 7 (29th March 2013) - Derosa, G.; Cicero, A. F. G.; Franzetti, I. G.; Querci, F.; Carbone, A.; Piccinni, M. N.; D'Angelo, A.; Fogari, E.; Maffioli, P.
Abstract Aims To evaluate which triple oral therapy between metformin + pioglitazone + sitagliptin and metformin + pioglitazone + glibenclamide can be more useful in improving glycaemic control and should be preferred in clinical practice. Methods During the 2‐year run‐in period, patients were instructed to take metformin monotherapy for the first year, then a combination of metformin and pioglitazone for the second year, then patients were randomized to add glibenclamide or sitagliptin to the dual combination of metformin and pioglitazone for another year. Results Body weight reached with sitagliptin at 36 months was lower than that reached with glibenclamide. Fasting plasma insulin and homeostasis model assessment of insulin resistance were significantly increased by triple therapy with glibenclamide and decreased by that with sitagliptin. While sitagliptin did not change homeostasis model assessment of β‐cell function, this value was significantly increased by glibenclamide. Fasting plasma proinsulin was not influenced by triple oral therapy including glibenclamide, while it was decreased by the therapy including sitagliptin compared to glibenclamide. Triple oral therapy with sitagliptin better improved β‐cell function measures compared with the glibenclamide therapy. Conclusions Sitagliptin should be preferred to glibenclamide as an addition to the metformin + pioglitazone combination for its better protection of β‐cell secretion and its neutral effect on body weight.